Sosialisasi Sistem Sistem Rekam Medis Elektronik Pada Puskesmas Desa Sumbersari Kabupaten Madiun - Crismantoro Budisaputro; Heru Widianto; Al Wafi Rahmaputri A (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
The availability of medical record files accurately and quickly when needed is one indicator of quality patient service so that patients feel well served. Correct and valid reports depend on the process of obtaining the data, therefore a management system is needed that is able to monitor the data processing process quickly and in real time. Currently the system running at the Sumbersari Community Health Center is implemented manually. The manual medical record system takes quite a long time plus the risk of being vulnerable to loss, damage and requires a large space to store the documents. Using a website-based medical record system is the right solution to solve this problem. So that all medical records personnel can quickly master the use of this system, assistance is needed in the form of socialization on the use of a website-based electronic medical records system